Factors associated with quit attempts and smoking cessation in Brazil: findings from the International Tobacco Control Brazil Survey. (September 2019) - Casado, L.; Thrasher, J.F.; Perez, C.; Santos Thuler, L.C.; Fong, G.T.
Abstract: Objectives: This study aimed to identify factors associated with attempting to quit and successful smoking cessation in a population-based sample of Brazilian smokers. Study design: This is a prospective cohort study. Methods: Data came from the first two waves of the International Tobacco Control Brazil Survey, conducted in 2009 and 2012/2013 in three cities: Rio de Janeiro, São Paulo, and Porto Alegre. Data were collected from 488 adults (aged ≥18 years) who smoked at Wave 1 and who were resurveyed at Wave 2. Crude and adjusted relative risks for two outcomes (making a quit attempt between Wave 1 and Wave 2 and successfully quitting by Wave 2) were estimated. Multivariable multilevel logistic regression models were used, whereby variables were added to the models in a series of blocks. Results: Nearly two-thirds (65.6%) of smokers attempted to quit between waves, and 23.4% had quit at Wave 2. Intention to quit smoking at Wave 1 was the only variable associated with attempt to quit by Wave 2 (odds ratio [OR] = 2.85; 95% confidence interval [CI] 1.64–4.94; P < 0.001). Smokers of higher socio-economic status (OR high versus low = 1.80; 95% CI 1.05–3.10; P = 0.03) and lower nicotine dependence (OR low Heaviness of Smoking Index [HSI] versus high HSI = 1.94; 95% CI 1.10–3.43; P = 0.02) were more likely to successfully quit. The presence of another adult smoker at home was negatively related to successful quitting (OR = 0.50; 95% CI 0.26–0.94; P = 0.03). Conclusions: These results are generally consistent with prior research and have potential to inform governmental interventions to promote tobacco cessation, particularly among disadvantaged groups. Highlights: First population-based study to assess the variables associated with quit attempts and quit success in Brazil. Our results are generally consistent with prior research. The study conclusions have potential to inform governmental interventions to promote tobacco cessation. ITC Brazil Survey findings can provide important support for guiding tobacco control policies in the country.